Voriconazole in lung transplant recipients – how worried should we be?. Issue 1 (21st October 2017) - Kulkarni, Hrishikesh S.; Witt, Chad A.
Abstract : The authors comment on Hamandi et al's insights (page 113 ) into the risk versus benefit of using voriconazole in lung transplant recipients, given the increasingly accepted risk of squamous cell carcinoma.